Molecular detection of human Plasmodium species in Sabah using PlasmoNextm multiplex PCR and hydrolysis probes real-time PCR - Lee, Ping Chin; Tzyy, Eric Jiann Chong; Yvonne AL Lim; Ching, Hoong Chew; Kek, Heng Chua (BioMed Central Ltd., 2015)
BACKGROUND: Malaria is a vector borne-parasitic disease transmitted through the bite of the infective female Anopheles mosquitoes. Five Plasmodium species have been recognized by World Health Organization (WHO) as the causative agents of human malaria. Generally, microscopic examination is the gold standard for routine malaria diagnosis. However, molecular PCR assays in many cases have shown improvement on the sensitivity and specificity over microscopic or other immunochromatographic assays.